Pax3 overexpression induces cell aggregation and perturbs commissural axon projection during embryonic spinal cord development. Issue 7 (27th February 2017) - Lin, Juntang; Fu, Sulei; Yang, Ciqing; Redies, Christoph
Abstract : Pax3 is a transcription factor that belongs to the paired box family. In the developing spinal cord it is expressed in the dorsal commissural neurons, which project ascending axons contralaterally to form proper spinal cord–brain circuitry. While it has been shown that Pax3 induces cell aggregation in vitro, little is known about the role of Pax3 in cell aggregation and spinal circuit formation in vivo. We have reported that Pax3 is involved in neuron differentiation and that its overexpression induces ectopic cadherin‐7 expression. In this study we report that Pax3 overexpression also induces cell aggregation in vivo. Tissue sections and open book preparations revealed that Pax3 overexpression prevents commissural axons from projecting to the contralateral side of the spinal cord. Cells overexpressing Pax3 aggregated in cell clusters that contained shortened neurites with perturbed axon growth and elongation. Pax3‐specific shRNA partially rescued the morphological change induced by Pax3 overexpression in vivo. Our results indicate that the normal expression of Pax3 is necessary for proper axonal pathway finding and commissural axon projection. In conclusion, Pax3 regulates neural circuit formation during embryonic development. J. Comp. Neurol. 525:1618–1632, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Pax3 overexpression induces cell aggregation and perturbs commissural axon projection in the developing spinal cord. Abbreviations: fp, floor plate; ilc, intermediate longitudinal commissural axons; mlc, medial longitudinal commissural axons.